Language as context for the perception of emotion - Barrett, Lisa Feldman (2007)
In the blink of an eye, people can easily see emotion in another person’s face. This fact leads many to assume that emotion perception is given and proceeds independently of conceptual processes such as language. In this paper we suggest otherwise and offer the hypothesis that language functions as a context in emotion perception. We review a variety of evidence consistent with the language-as-context view and then discuss how a linguistically relative approach to emotion perception allows for intriguing and generative questions about the extent to which language shapes the sensory processing involved in seeing emotion in another person’s face.